Strategic leadership skills as a moderate of the impact of environmental challenges on effective management of the environment according to the model (VUCA Prime) - AL Najm, Hasan A. K.; AL Kubaisi, Salah Aldeen A. (Journal of Economics and Administrative Sciences, 2020)
Purpose – The main purpose of this research is to highlight the main role of strategic leadership skills for top managements in accessing to effective management in accordance with the (VUCA Prime) methodology in (VUCA) environment as Miniature virtual environment, which refers to (Volatility), (Uncertainty), (Complexity), and (Ambiguity).methodology – To achieve the research objective, this study selected the quantitative approach in research design, Questionnaire was used as the main instrument for data collection, the sample comprised the opinion poll (106) individual who functions as a head department. (Structural equation modelling by (Smart Pls3) was used for data analysis.Findings: Leaders at top managements possess high skills and expertise, but the Leaders have not used their skills rightly, with the extreme dealing caution against risk. This was reflected in the diversity of services provided by Iraqi private banks.Research limitations: The researcher suffered many difficulties, including the lack of transparency and the country's turbulent circumstances, and the shortage of the number of Collaborating banks, which affected the adequacy of the statistical sample because most of the top management of those banks fear the result of the assessment, which led to inaccurate answers avoided with using appropriate statistical methods.   Practical implications: The research discusses the skills of strategic leadership and how it contributes to changing the impact of environmental challenges, which face the top managements of banks, which contributes to the development of a clear method, leading the top managements to effective management diagnosis of failure points and trying to avoid them.Social implications: The top managements access to the Effectiveness will lead to Prosperity of the Iraqi private banks and increase the banks' s ability to adapt to the environment, which will lead to the results of economic prosperity in the country. through the skills that the management possess and achieving the goals of communicating with all stakeholders to follow the best ways to achieve the social goals of the skills. Originality: The scientific value of the research is research in three important variables for modern organizations which are environmental skills and challenges, skills and Effective management. Especially for their association with an important phenomenon which is leadership, assuming positive responses in motivating top managements to use their skills in managing those challenges, to contribute to the development of an integrated system of adaptation, considering the Iraqi environment that embodies (VUCA) environment.